Benchmarking at Majlis Perbandaran Kuantan / Norlaila Abdullah...[et al.] - Abdullah, Norlaila; Husin, Zuhariah; Abdul Rahman, Nurulhuda; Ahmad Azam, Faizah Azam (2005)
This study depicts a scenario of a local government entity implementing some management best practices (MBP) towards attaining the highest level of competitive advantage at par with similar world class entities locally and abroad. The prime objective of the study is to clearly visualize the process of adopting and implementing proven techniques working to the best advantage of the practice owner. Some of the proven benchmarking exercises highlighted include the interactive public complaints system, sanitary landfill system, public awareness and educational programs and activities management, system on information computer technology, customer satisfaction, usage of key performance indicators and work culture (shared values). Other emerging practices are cited relating to petty trader and parking management systems. Some members of the top management hierarchy have been interviewed to physically capture the strategic planning, implementation and adoption of some perceived MBP in addition to retrieval of records and documents furnished by the entity to substantiate prior years' achievements.